Newly formed chambers of the benthic foraminifera Amphistegina lobifera exposed to electric current, May 2023 - Federica Rebecchi; Davide Lattanzi; Sigal Abramovich; Patrizia Ambrogini; Fabrizio Frontalini; Christiane Schmidt (PANGAEA, 2025)
This dataset provides measurements of the growth rate of the benthic foraminifera Amphistegina lobifera, exposed to electric currents, based on the number of newly formed chambers. Growth was assessed using the green calcein probe, a fluorescent compound. The data were collected after a one-month period in May 2023 during the second of a two-part experiment by counting calcein-labelled chambers under an epifluorescence stereomicroscope (Zeiss stereomicroscope Discovery.V8). This dataset provides insights into the potential effects of electric currents on the growth and calcification processes of benthic foraminifera.
In: Rebecchi, F et al. (2025): Effects of electric current on growth, chlorophyll a content, pulse amplitude modulation response, and new chamber formation of the foraminifera Amphistegina lobifera [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.983600